Crusade Propaganda and Ideology: Model Sermons for the Preaching of the Cross - Maier, Christoph T. (Cambridge University Press, 2003)
This book presents an edition of seventeen manuscript sermon texts for the preaching of the crusades - unique sources for the study of the crusades and medieval preaching, two vibrant areas of medieval studies. The majority of these texts, printed in Latin and in English translation, have never been published before